2020
DOI: 10.1111/ijfs.14680
|View full text |Cite
|
Sign up to set email alerts
|

An interdisciplinary and participatory methodology to improve user acceptability of root, tuber and banana varieties

Abstract: Breeding programmes for root, tuber and banana (RTB) crops have traditionally considered consumer demand for quality characteristics as low priority against other considerations such as yield and disease resistance. This has contributed to low levels of adoption of new varieties and its potential benefits. To address these challenges, an interdisciplinary five-step methodology was developed to identify demand for quality characteristics among diverse user groups along the food chain. The methodology includes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
111
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 43 publications
(111 citation statements)
references
References 13 publications
0
111
0
Order By: Relevance
“…The survey was carried out in eight rural communities of central Benin belonging to the Districts of Dassa-Zoum e and Djidja. A survey was undertaken using the multidisciplinary methodology described by Forsythe et al (2021). Participants were yam farmers, processors/cookers and consumers of boiled yam, who were selected randomly from different localities.…”
Section: Gendered Food Mapping In Rural Communitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The survey was carried out in eight rural communities of central Benin belonging to the Districts of Dassa-Zoum e and Djidja. A survey was undertaken using the multidisciplinary methodology described by Forsythe et al (2021). Participants were yam farmers, processors/cookers and consumers of boiled yam, who were selected randomly from different localities.…”
Section: Gendered Food Mapping In Rural Communitiesmentioning
confidence: 99%
“…It involved several successive steps such as qualitative surveys all along the food chain to identify quality criteria of a good cassava crop and product, effective participation of processors to identify the ability of genotypes to make a good product, and a 'all-in-one' method coupling hedonic test, JAR 'Just All Right' test, CATA 'Check All That Apply' questions to assess the acceptability and preferences of products by a large number of consumers. Furthermore, Forsythe et al (2021) reported an interdisciplinary and participatory methodology to assess user acceptability of root, tuber and banana varieties, with the ultimate aim of informing breeding programmes in trait selection. This study aimed to identify the quality characteristics (morphological, postharvest, physicochemical, technological and sensory characteristics) of raw and boiled yam, required by producers, traders, processors and consumers in Benin, and how they influence varietal preferences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Pivot Table feature is a user-friendly and easy-to-use tool, which is relevant for the kinds of analysis which is required in a trait preference evaluation, following FAO (2016). Characteristics of preferred traits were assigned weights according to how they were prioritised and the importance they were given by respondents following Forsythe et al (2020). To aggregate the characteristics into one table, we gave each of them weights according to how they were prioritized, and the importance they were given by respondents.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…It involved several successive steps, including qualitative surveys all along the food chain to identify quality criteria of a good cassava crop and product, and effective participation of processors to identify the ability of new genotypes to make a good product. Forsythe et al (2021) adapted this approach in a multidisciplinary methodology to better understand end-users' demand of good quality root, tuber and banana (RTB) crop and products.…”
Section: Introductionmentioning
confidence: 99%